Proceedings of the 27th ACM Conference on on Innovation and Technology in Computer Science Education Vol. 1 2022
DOI: 10.1145/3502718.3524739
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Learning via Cisco Packet Tracer to Enhance the Teaching of Computer Networks

Abstract: Teaching and learning computer networks is a crucial part of a computing undergraduates' education. However, it is an abstract topic with theory that can be challenging for students to comprehend. Simulation-based learning can be used as a teaching tool to enhance networking-based lecture topics and help students more easily understand and visualise how it really works in a safe, user-friendly environment. One such simulation tool, Cisco Packet Tracer, can be used to good effect, and this paper reports on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Other learning models using Packet Tracer (Vijayalakshmi, Desai & Raikar, 2016;Zhang, Liang & Ma, 2012;Janitor, Jakab & Kniewald, 2010) offer basic introductions and application/transport layer exercises but neglect crucial network and link layer aspects. Further limitations can be observed in models focusing solely on router configuration via device commands (Javid, 2014;Noor, et al, 2018), or topics like Internet of Things (IoT) simulation (Gwangwava & Mubvirwi, 2021;Almalki, 2020;Chaudhari, Joshi, Joshi & Kumar, 2020;Gumina & Tang, 2021), or basic routing table manipulation, wireless, and firewall configurations (Allison, 2022;Abdrabou & Shakhatreh, 2021;Reddy, et. al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Other learning models using Packet Tracer (Vijayalakshmi, Desai & Raikar, 2016;Zhang, Liang & Ma, 2012;Janitor, Jakab & Kniewald, 2010) offer basic introductions and application/transport layer exercises but neglect crucial network and link layer aspects. Further limitations can be observed in models focusing solely on router configuration via device commands (Javid, 2014;Noor, et al, 2018), or topics like Internet of Things (IoT) simulation (Gwangwava & Mubvirwi, 2021;Almalki, 2020;Chaudhari, Joshi, Joshi & Kumar, 2020;Gumina & Tang, 2021), or basic routing table manipulation, wireless, and firewall configurations (Allison, 2022;Abdrabou & Shakhatreh, 2021;Reddy, et. al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Packet Tracer software has been used around the globe to enhance students learning. Especially during the COVID-19 pandemic (Allison, 2022). A recent review of the literature found that, since the outbreak of the pandemic, more and more institutions have adopted PT as a teaching tool to foster remote learning.…”
Section: Related Workmentioning
confidence: 99%
“…A study conducted in Malaysia by Allison (2022) developed a Survey on the Challenges Faced by the Lecturers in Using PT in Computer Networking Courses. Their idea was to identify the problems faced by teachers throughout the teaching and learning process, even with the help of instructional simulations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to advancements in technology in higher education settings, the significance of computer networks is amplified. Computer networks aid in seamless communication, network infrastructures, data transfer, and collaboration across devices, systems, and users [2]. The traditional methods of teaching in higher education for computer networking frequently encounter challenges in providing a comprehensive understanding of complex networking concepts to learners [3].…”
Section: Introductionmentioning
confidence: 99%